Determination of cumulative rainfall threshold trigger of landslides in Grindulu watershed as an early warning effort - Arina Miardini; Pranatasari Dyah Susanti (Journal of Degraded and Mining Lands Management, 2020)
Landslides are one of the natural disasters that cause severe damage to life. The frequency of landslide has increased with global climate change and population growth, so early warning efforts are needed. Rain is a trigger factor for landslides can be used as an approximate model for disaster prevention and mitigation through the estimation of rainfall threshold. The purpose of this study was to determine the characteristics and threshold of rainfall that triggered landslides in the Grindulu watershed. The method used is the Cumulative Rainfall Threshold (CT), this method compares the amount of rainfall for the last 3 days (72 hours) with rainfall 15 days before. In the Grindulu watershed, landslides occur during 3-day cumulative daily rains ranging from 23-464 mm, whereas in the 15 days before the events range between 67-756.5 mm. Estimates of lower threshold rainfall are determined linear so that the equation P3 = 0.4675 P15-46.9 is obtained with the value R2 = 0.5774The threshold value of rainfall triggers a landslide in the Grindulu watershed when the cumulative rainfall of 3 days is 40 mm and 15 days before the event is 320 mm. The determination of rain threshold is expected to increase community preparedness for landslides.